Flexible Ion‐Conducting Composite Membranes for Lithium Batteries. Issue 14 (12th May 2015) - Aetukuri, Nagaphani B.; Kitajima, Shintaro; Jung, Edward; Thompson, Leslie E.; Virwani, Kumar; Reich, Maria‐Louisa; Kunze, Miriam; Schneider, Meike; Schmidbauer, Wolfgang; Wilcke, Winfried W.; Bethune, Donald S.; Scott, J. Campbell; et al.
<x xml:space="preserve">Abstract</x> The use of metallic lithium anodes enables higher energy density and higher specific capacity Li‐based batteries. However, it is essential to suppress lithium dendrite growth during electrodeposition. Li‐ion‐conducting ceramics (LICC) can mechanically suppress dendritic growth but are too fragile and also have low Li‐ion conductivity. Here, a simple, versatile, and scalable procedure for fabricating flexible Li‐ion‐conducting composite membranes composed of a single layer of LICC particles firmly embedded in a polymer matrix with their top and bottom surfaces exposed to allow for ionic transport is described. The membranes are thin (<100 μm) and possess high Li‐ion conductance at thicknesses where LICC disks are mechanically unstable. It is demonstrated that these membranes suppress Li dendrite growth even when the shear modulus of the matrix is lower than that of lithium. It is anticipated that these membranes enable the use of metallic lithium anodes in conventional and solid‐state Li‐ion batteries as well as in future LiS and LiO2 batteries.